2012
DOI: 10.1007/s13404-012-0048-7
|View full text |Cite
|
Sign up to set email alerts
|

The combination effects of trivalent gold ions and gold nanoparticles with different antibiotics against resistant Pseudomonas aeruginosa

Abstract: Despite much success in drug design and development, Pseudomonas aeruginosa is still considered as one of the most problematic bacteria due to its ability to develop mutational resistance against a variety of antibiotics. In search for new strategies to enhance antibacterial activity of antibiotics, in this work, the combination effect of gold materials including trivalent gold ions (Au 3+ ) and gold nanoparticles (Au NPs) with 14 different antibiotics was investigated against the clinical isolates of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Results revealed that the antioxidant activity increases by increasing the concentration of nanoparticles. Azizi et al [20] reported the same result where the scavenging of DPPH radicals was found to be increasing as the concentration of ZnO NPs increases [22]. The cytotoxicity of ZnO NPs against brine shrimp larvae indicated the non-toxic effect of ZnO NPs.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Results revealed that the antioxidant activity increases by increasing the concentration of nanoparticles. Azizi et al [20] reported the same result where the scavenging of DPPH radicals was found to be increasing as the concentration of ZnO NPs increases [22]. The cytotoxicity of ZnO NPs against brine shrimp larvae indicated the non-toxic effect of ZnO NPs.…”
Section: Discussionmentioning
confidence: 68%
“…Similar results were obtained when Nazari et al [19] analyzed the effect of gold nanoparticles (Au NPs) in combination with fourteen different β-lactam antibiotics against E. coli, Pseudomonas aeruginosa and Staphylococcus aureus. The results showed that Au NPs did not enhance the antibacterial effect of antibiotics at tested concentration [20]. The enhanced antimicrobial behavior of IPM with ZnO NPs was observed in K. pneumoniae (#1).…”
Section: Discussionmentioning
confidence: 88%
“…The use of antibiotics in combination with diff erent compounds is an approach to overcome the problem of antibiotics resistance (27). Enhancing the antibacterial eff ect of the diff erent antibiotics used in combination with silver or zinc oxide nanoparticles were previously reported (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Their finding suggested that using the combination of sub-inhibitory concentrations of Au3 + and methicillin, erythromycin, nalidixic acid or vancomycin may be a promising new strategy for the treatment of highly resistant P. aeruginosa infections. However, more laboratory and molecular tests are required to be done in order to determine the effects of Au3 + and AuNPs in combination with antibiotics on P. aeruginosa cell wall permeability and their efflux pumps [131]. Antibacterial activity of gold nanoparticle has been shown in the Table 1 (Fig.…”
Section: Goldmentioning
confidence: 99%